Molecular Cloning and Induced Expression of Six Small Heat Shock Proteins Mediating Cold-Hardiness in Harmonia axyridis (Coleoptera: Coccinellidae) - Wang, Hui-Juan; Shi, Zuo-Kun; Shen, Qi-Da; Xu, Cai-Di; Wang, Bing; Meng, Zhao-Jun; Wang, Shi-Gui; Tang, Bin; Wang, Su (Frontiers in Physiology, 2017)
The main function of small heat shock proteins (sHSPs) as molecular chaperones is to protect proteins from denaturation under adverse conditions. Molecular and physiological data were used to examine the sHSPs underlying cold-hardiness in H. axyridis. Complementary DNA sequences were obtained for six Harmonia axyridis sHSPs based on its transcriptome, and the expression of the genes coding for these sHSPs was evaluated by quantitative real-time PCR (qRT-PCR) in several developmental stages, under short-term cooling or heating conditions, and in black and yellow females of experimental and overwintering populations under low-temperature storage. In addition, we measured water content and the super cooling and freezing points (SCP and FP, respectively) of H. axyridis individuals from experimental and overwintering populations. The average water content was not significantly different between adults of both populations, but the SCP and FP of the overwintering population were significantly lower than that of the experimental population. Overall, the six sHSPs genes showed different expression patterns among developmental stages. In the short-term cooling treatment, Hsp16.25 and Hsp21.00 expressions first increased and then decreased, while Hsp10.87 and Hsp21.56 expressions increased during the entire process. Under short-term heating, the expressions of Hsp21.00, Hsp21.62, Hsp10.87, and Hsp16.25 showed an increasing trend, whereas Hsp36.77 first decreased and then increased. Under low-temperature storage conditions, the expression of Hsp36.77 decreased, while the expressions of Hsp21.00 and Hsp21.62 were higher than that of the control group in the experimental population. The expression of Hsp36.77 first increased and then decreased, whereas Hsp21.56 expression was always higher than that of the control group in the overwintering population. Thus, differences in sHSPs gene expression were correlated with the H. axyridis forms, suggesting that the mechanism of cold resistance might differ among them. Although Hsp36.77, Hsp16.25, Hsp21.00, and Hsp21.62 regulated cold- hardiness, the only significant differences between overwintering and experimental populations were found for Hsp16.25 and Hsp21.00.